Endoscopic Precise Resection of Haglund's Deformity Using K-wire (Novel Technique) - KR Rohit; Parthiban Jeganathan; Sai Vineet Damodar Premkumar; AK Sanjay; Suresh Perumal (Journal of Orthopedics and Joint Surgery)
The objective of our study is to assess the result of endoscopic calcaneoplasty in patients diagnosed with Haglund's deformity. The first-line management for Haglund's deformity is conservative treatment. The various options available are open excision, calcaneal osteotomy, and endoscopic calcaneoplasty. Patients, after fulfilling the inclusion criteria and obtaining informed consent, were taken up for study. Clinical and radiological examinations were done prior to the study. Our study included 15 patients, 11 of whom were female and four were male. Patients were evaluated preoperatively and postoperatively with an American Orthopaedic Foot and Ankle Society (AOFAS) score. The average follow-up of our study was 26 months, and zero patients were lost to follow-up. According to the AOFAS score, 14 patients showed results in the excellent range, with one patient showing good results, and the average resumption to activity was 4 weeks. There were no complications in our study. We conclude that endoscopic calcaneoplasty is a safe and effective technique for addressing Haglund's deformity. It has a steep learning curve with no complications and a faster resumption of activity.